Efficacy of Autologous Microfat Graft on Facial Handicap in Systemic Sclerosis Patients. Issue 3 (March 2016) - Sautereau, Nolwenn; Daumas, Aurélie; Truillet, Romain; Jouve, Elisabeth; Magalon, Jéremy; Veran, Julie; Casanova, Dominique; Frances, Yves; Magalon, Guy; Granel, Brigitte
Abstract : Background: Autologous adipose tissue injection is used in plastic surgery for correction of localized tissue atrophy and has also been successfully offered for treatment of localized scleroderma. We aimed to evaluate whether patients with systemic sclerosis (SSc) and facial handicap could also benefit from this therapy. Methods: We included 14 patients (mean age of 53.8 ± 9.6 years) suffering from SSc with facial handicap defined by Mouth Handicap in Systemic Sclerosis Scale (MHISS) score more than or equal to 20, a Rodnan skin score on the face more than or equal to 1, and maximal mouth opening of less than 55 mm. Autologous adipose tissue injection was performed under local anesthesia using the technique of subcutaneous microinjection. The main objective of this study was an improvement of the MHISS score 6 months after the surgical treatment. Results: The procedure was well tolerated. We observed a mean decrease in the MHISS score of 10.7 points (±5.1; P < 0.0001) at 6 months (35% improvement). Secondary efficacy parameters assessing perioral skin sclerosis, maximum mouth opening, sicca syndrome, and facial pain significantly improved at 3 and 6 months postsurgery. At a 6-month follow-up, 75% of patients were satisfied or very satisfied of the adipose tissue microinjection therapy. Conclusions: Our study suggests that subcutaneous perioral microfat injection in patients with SSc is beneficial in the treatment of facial handicap, skin sclerosis, mouth opening limitation, sicca syndrome, and facial pain. Thus, this minimally invasive approach offers a new hope for face therapy for patients with SSc.